"Écho" d'une rencontre virtuelle : Vers une ethnographie de la production audiovisuelle - Boudreault-Fournier, Alexandrine (Anthropologica, 2022)
Echo is the name of an ethnographic project whose aim is to create a "space of correspondence" in which two accomplished Cuban artists (one living in Montreal and the other in Santiago de Cuba) meet on a virtual stage to compose an original piece of music. Beyond a technical challenge, given the limitations characterizing the socialist island, theis experiment develops on the theme of the "native land" as a source of inspiration by creating an intersubjective space of exchange between two musicians who share the same roots. Based on an anthropological approach that borrows from the concept of relational art, this article explores the process of creation of a virtual space of encounter, as well as the technological challenges related to it. The text, by adopting a methodology that considers the concepts of aesthetics and technology seriously, allows one to raise areas of research using a creative approach that has, up to now, been underestimated in anthropology.